Clusters as an element of regional specialisation based on the example of Lower Silesia - Drelich-Skulska, Bogusława; Jankowiak, Anna H. (Klastry jako element specjalizacji regionalnej na przykładzie Dolnego Śląska, 2019)
Strategy Europe 2020 is intended to support smart specialisation, i.e. the innovative development of individual regions which benefit from what constitutes their specific and unique features. Regions have to indicate their strong points, and focus their activities on those areas of science and innovativeness which are complimentary to a given region’s resources and ultimately will create or strengthen its comparative advantages. The aim of this article is to present the concept itself, as well as the theoretical principles of smart specialisation in a regional dimension. In turn, they will become the basis for examining the role and the importance of clusters in the development of the regional specialisation of Lower Silesia. At the same time, the authors studied the possibilities of creating new clusters and their relevance for mapping out future areas of specialisation of the region, corresponding with the objectives of Strategy Europe 2020
Biblioteka Regionalisty, 2019, Nr 19, s. 37-49
Keywords: Dolny Śląsk